ABSOLUTE CONFIGURATION OF MEDICINAL AND AROMATIC NATURAL PRODUCTS BY VIBRATIONAL CIRCULAR DICHROISM - Joseph-Nathan, P. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Vibrational circular dichroism (VCD) is an emerging spectroscopic method for the absolute configuration determination of organic molecules, either isolated from nature or derived by synthetic procedures. VCD is a general method in which an optically active meassurement can be compared to calculations performed using quantum mechanical equations in the ground state of the molecule. Comparison of both results, the measured spectrum and the one calculated using density functional theory (DFT), directly provides for molecules of moderate complexity the absolute configuration of the studied compound and its conformational preference in solution. Thus, it is a method that allows determining the absolute configuration without reference to a rule or to the need of structural correlation. VCD can be seen as the extension of classical circular dichroism, now also called electronic circular dichroism, from the ultraviolet and visible regions of the electromagnetic spectrum into the infrared region, or alternatively it can be seen as the determination of an optically active infrared spectrum. The main difficulty in measuring VCD spectra resides in the fact that bands that are being optically active in the infrared region are of very low intensity, in fact ten thousand to hundred thousand times less intense than classical infrared bands, thereby placing great demands on optical and electronic requirements of an instrument. Associated with this is the mercury-cadmium-telluride detector, used in VCD spectrophotometers, which operates at liquid nitrogen temperature. Results that allow highlighting some of the benefits and limitations of this methodology applied to several natural products will be presented. These include aromatic molecules like camphor, limonene, menthol, myrtenal or cedrene, and medicinal molecules like the distinction of both diastereoisomers of the tropane alkaloid 6-hydroxyhyosciamine, the evaluation of verticillanes, which are precursors of taxol, and physostigmine. Regarding calculations, it has to be mentioned that a reasonable balance between computer time and accuracy can be settled when the DFT calculations are performed using the hybrid functional B3LYP and the 6-31G(d) or 6-31G(d,p) basis sets, although in some cases more complex functional and higher basis sets could be required. For the herein studied molecules, this results in very variable computer times, ranging from 3 to 40 h per conformer, when using commercial Gaussian 03 software on a PC system operated at 3 GHz with 2 Mb RAM.